2023
DOI: 10.3390/ijerph20042937
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Inflammatory Response in Post-Traumatic Stress Disorder (PTSD): A Systematic Review on Peripheral Neuroimmune Biomarkers

Abstract: Several heterogeneous pathophysiology pathways have been hypothesized for being involved in the onset and course of Post-Traumatic Stress Disorder (PTSD). This systematic review aims to summarize the current evidence on the role of inflammation and immunological dysregulations in PTSD, investigating possible peripheral biomarkers linked to the neuroimmune response to stress. A total of 44 studies on the dysregulated inflammatory and metabolic response in subjects with PTSD with respect to controls were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 68 publications
1
12
0
1
Order By: Relevance
“…Immune and inflammatory mechanisms have been implicated in the progression of several neurodegenerative disorders, including AD [81], frontotemporal dementia [82], and Parkinson's disease [83]. PTSD has been consistently associated with increases in certain markers of systemic inflammation [24,84], though it is not known to what extent these correlate with central nervous system inflammatory activity. In the current review, these findings were replicated in the context of possible links with neurodegeneration, with results specifically implicating CRP, IL-6 and soluble TNF-α receptor II.…”
Section: Integration Of Existing Results On Biomarkers Of Neurodegene...mentioning
confidence: 99%
“…Immune and inflammatory mechanisms have been implicated in the progression of several neurodegenerative disorders, including AD [81], frontotemporal dementia [82], and Parkinson's disease [83]. PTSD has been consistently associated with increases in certain markers of systemic inflammation [24,84], though it is not known to what extent these correlate with central nervous system inflammatory activity. In the current review, these findings were replicated in the context of possible links with neurodegeneration, with results specifically implicating CRP, IL-6 and soluble TNF-α receptor II.…”
Section: Integration Of Existing Results On Biomarkers Of Neurodegene...mentioning
confidence: 99%
“…Chronic stress and past traumatic events have been shown to increase the production of pro-inflammatory cytokines, which upregulate the enzyme IDO1, leading to increased production of KYNA and quinolinic acid, both of which are involved in NMDA transmission and neurotoxicity. 51 , 52 Animal models have demonstrated that exposure to stressors increases KYNA levels in rats. 53 , 54 Inhibiting KYNA synthesis has been shown to reduce fear discrimination impairment caused by stressors, highlighting the role of KYNA in stress response and traumatic experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctions in these processes can disrupt information flow between brain regions, potentially contributing to cognitive deficits and altered emotional processing which are observed in PTSD ( Girgenti et al, 2017 ). Additionally, dysregulation in the metabolism and hormonal levels can impact stress responses, contributing thus, to the development of PTSD symptoms ( Dell’Oste et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%